Shifting microbial communities perform anaerobic oxidation of methane and methanogenesis in sediments from the Shenhu area of northern south China sea during long-term incubations - Kong, Yuan; Lei, Huaiyan; Cheng, Weidong; Wang, Bin; Pan, Fulong; Huang, Fanfan (Frontiers in Earth Science, 2022)
Microbial communities and their associated metabolic activities, methanogenesis and anaerobic oxidation of methane (AOM), are the key components of carbon biocycles in continental margin sediments. The composition and diversity of microbial communities in a methanic environment have been widely investigated, but identifying direct correlations between microbial communities and their activities remains a challenge. Here, we investigated shifting microbial communities that performed methanogenesis and AOM in long-term incubations. AOM, methanogenesis, sulfate reduction and iron reduction occurred during the incubation, and 16S rRNA gene sequencing showed that some bacteria were maintained or even enriched during the incubation compared to the environmental samples. In contrast, archaeal diversity was reduced, and only some uncultured archaea belonging to the phylum Bathyarchaeota were enriched after treatment with a high sulfate concentration (29.38mM), suggesting that sulfate might promote their enrichment. Well-known anaerobic methanotrophic archaea (ANME) were not detected, and SEEP-SRB1, which is in syntrophy with ANME, decreased to approximately zero after the incubation. The abundance of known methanogens, such as genera Methanococcoides and Methanosarcina, increased slightly in some incubations but was still present at a low relative abundance (<0.15%). Incubation with a lower sulfate concentration (4 mM) and higher iron content resulted in greater δ13CO2 accumulation, indicating that iron may be the additional electron acceptor for AOM. Based on these results, other unknown or unconventional phylotypes or pathways of methanogenesis and AOM may occur during the incubation. Thus, the diversity of methanogens and anaerobic methanotrophs warrants further investigation.